Effects of Dietary Supplementation With Soybean And Canola Oil on Lipid Profiles and Heart in Swiss Albino Mice - Sarif, MA; Akter, L; Haque, Z; Islam, MR (Annals of Bangladesh Agriculture, 2022)
Soybean and canola oil are two of the most widely used cooking oils on the planet. The experiment was conducted to study the dose dependent toxicity of dietary supplementation of soybean and canola oil on heart of Swiss albino mice. In the study, 30 male Swiss albino mice aged 6 weeks were randomly assigned to one of five equivalent groups: Group A was considered as control by feeding rat pellet only, group B1 and B2 were supplemented with 25 and 35 ml soybean oil/kg pellet and group C1 and C2 were provided with 25 and 35 ml canola oil/kg pellet, respectively for 60 days, adopting established research procedure. After conducting the experimental period, blood and organ (heart) samples were collected from control and oil supplemented mice through deep anesthesia. The biochemical study of blood revealed that maximum total cholesterol, triglycerides and high density lipoprotein values (153.85 ± 0.44, 88.82 ± 0.37 and 105.50 ± 0.33 mg/dl) were found statistically significant (P<0.05) in soybean oil supplemented group (B2) as compared to other groups (B1, C2, C1 and A). Gross study revealed that highest mean weight of heart (0.41 ± 0.01 g) was recorded in soybean oil supplemented group (B2) significantly (P<0.05) in comparison to other experimental groups B1, C2, C1 and A. Histopathological study revealed that marked lymphocytic infiltration was found in the ventricular wall of the heart of high dose supplemented groups. So, it may conclude that dietary supplementation of soybean and canola oil have adverse effects on blood lipid profiles and heart of mice.Ann. Bangladesh Agric. (2021) 25 (2) : 87-95